Study Of Transmissibility Of Laminated Rubber-Metal Spring - Salim, Mohd Azli (UTeM, 2016)
Laminated rubber-metal bearing has been well-known as a vibration isolator to dissipate vibration energy. However, most of existing works on the bearing especially the mathematical models consider only the performance of the bearing due to the static force. The main objective of this study is therefore to develop mathematical model to characterize the isolation performance of the bearing; called here laminated rubber-metal spring (LRMS). Mathematical models for ‘transmissibility’ are developed by using three different approaches: (i) lumped parameter system, (ii) distributed parameter system and (iii) discrete lumped parameter system. The first approach uses assumption of massless rubber, where the rubber layers are simply modelled by using spring and damper elements. The second approach employs impedance technique derived from wave propagation across a cylindrical rubber. In this approach, the internal resonances can be predicted. And the third approach uses a method of dividing a rubber layer into multiple elements of masses and springs in order to predict the equivalent internal resonance as in the second approach. It is found that by adding more metal plates in the rubber, more resonances exist in the transmissibility which can degrade the isolation performance. However, the isolation at high frequencies is improved compared with that of the spring without embedded metal plates. The resonances can be reduced by adding more damping to the rubber. For the experimental work, the LR-MS samples with five different number of embedded metal plates were fabricated using Standard Malaysian Rubber Constant Viscosity (SMR-CV). A test rig for this purpose was also fabricated based on international standards. The measured data of force transmissibility shows good agreement with the proposed mathematical model. Last but not least, there parametric study is also discussed in this thesis.